Effects of EFB biochar on growth and phytochemical content of Labisia pumila Benth - Omar Baki, Siti Norayu (2017)
Kacip Fatimah (Labisia pumila) is reputed to have great medical value for Malay women in Malaysia. As the national herbal industry, the demand is increasing rapidly, however, the supply of raw materials from the natural source is getting scarce, unreliable and unsustainable. Cultivation of L. pumila has many constrains especially of poor root development and sensitivity to the microenvironment. Biochar has been recognized to improve the rate of plant growth via media tilth and nutrient availability, thus may improve plant productivity. However, very few cases of biochar have been reported on medicinal plants. Since biochar has been recognized to improve plant growth and possibly quality of the herb, it will be useful to investigate the effect of EFB biochar mix with growing media of L. pumila in enhancing both the growth and quality of L. pumila, especially in terms of the phytochemical content. Therefore, two studies were conducted with the objectives, (i) to study the effect of different rates of EFB biochar on the growth and development of three varieties of L. pumila Benth. and (ii) to identify and classify the phytochemical compounds present in L. pumila varieties affected by the EFB biochar amendment. Prior to study, soilless media mixed with EFB biochar was characterized based on chemical properties. Result showed the pH, CEC, moisture content, water holding capacity of the soilless media of L. pumila were increased when added with EFB biochar with the following ranges: pH (5.6 to 6.1), CEC (64.2 to 72.2 cmol (+) kg⁻¹, moisture content (25.3% to 29.2%) and water holding capacity (40.5% to 43.8%). The bigger BET surface area and pore volume were found as 45.76 m²g⁻¹ and 0.008 ccg⁻¹, respectively. In first study, four rates of biochar (0%, 3%, 6% and 9% (w/w)) were applied to the three varieties of L. pumila (var pumila, var alata and var lanceolata) and data on L. pumila growth was collected in four harvesting times (30, 60, 90 and 120 days of treatment). Generally, plant applied with EFB biochar exhibited significant difference in leaf area, chlorophyll content (TCC), root surface area, total dry biomass (TDB), relative growth rate (RGR) and leaf macro-nutrient content. All these growth parameters except total leaf area showed that L. pumila plants treated with 3% and 6% shown no significant different. Meanwhile, total leaf area of L. pumila treated with 6% of EFB biochar gained higher value compared to other treatments. The result indicates that growth parameters for L. pumila reduced significantly with the highest rate 9% of EFB biochar. Labisia pumila var pumila and var lanceolata showed higher improvement compared to var alata. The growth parameters showed higher values at 120 days after treatment. The result showed that the application of EFB biochar at rate 3% and 6% gave significantly higher growth of L. pumila compared to 9% of EFB biochar. In second study, one rate of EFB biochar 6% w/w was chosen and 0% (without biochar application) w/w to investigate the enhancement of secondary metabolites production of L. pumila. In study 2, an experiment of 2 rates of EFB biochar vs 3 varieties of L. pumila vs 3- time harvest has been conducted. The two rates of biochar (0% and 6% w/w) were applied to the three varieties of L. pumila (var pumila, var alata and var lanceolata) and the data has been taken in three harvesting times (40, 80 and 120 days of treatment). From the result showed that total phenolics (TP) content in 120 days treatment did not change in all the combined treatment except for var lanceolate. Meanwhile, total flavonoid (TF) content of L. pumila seedlings treated with 6% of EFB biochar had lower value compared to untreated plants. The highest production of TF content was obtained in var alata at 80 days after treatment when no EFB biochar applied. The secondary metabolites harvest index of L. pumila in non-treated plants and plants treated with 6% of EFB biochar were higher at 40 days of treatment. By using thin layer chromatography (TLC) method to the three varieties of L. pumila showed the presence of gallic acid, ferulic acid and caffeic acid in phenolic group, meanwhile in the flavonoid group presence of quarcetin and kaempferol. The result from this study indicated the potential of EFB biochar in improving the L. pumila growth with the optimum application rate of 6% EFB biochar. From the research findings, it can be concluded that the application of EFB biochar as soilless media amendment can enhanced the growth of L. pumila plants, however there we no significant in the production of secondary metabolite on treated plants, specifically, total phenolics and total flavonoid content.